Inovasi “Daakian” Sebagai Transformasi Pelayanan Kartu Identitas Anak di Kabupaten Bojonegoro - Farras Dewi Yuanita; Kalvin Edo Wahyudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Bojonegoro Regency has a low rate of Kartu Identitas Anak (Child Identity Card) issuance, reaching only 34.75% of the national target, which should have been 50% in 2023. The factors hindering the issuance of Kartu Identitas Anak in Bojonegoro Regency include a lack of public awareness, the absence of regulations requiring the use of Kartu Identitas Anak for any child-related identification purposes, a lack of support from other institutions or agencies, and inadequate infrastructure. To address this, Dinas Kependudukan dan Pencatatan Sipil (the Civil Registry Office of Bojonegoro Regency) launched the "Daakian" innovation in 2021, aimed at increasing the issuance of Child Identity Cards in Bojonegoro Regency. This study aims to understand and analyze the implementation of the Daakian innovation service in Bojonegoro Regency. The research method used is descriptive qualitative. Data collection involved interviews, observations, and documentation. This study uses Rogers' Innovation Theory, which consists of 1) Relative Advantage, 2) Compatibility, 3) Complexity, 4) Trialability, and 5) Observability. The technique for determining informants uses purposive sampling and snowball sampling. The results of this study indicate that the implementation of the Daakian Innovation in Bojonegoro Regency has been successful. This success is attributed to the Daakian Innovation providing greater ease for the public in Kartu Identitas Anak compared to the previous service. This ease has attracted public interest in obtaining Kartu Identitas Anak, which has positively impacted the increase in Kartu Identitas Anak issuance in Bojonegoro Regency.